Estimating the local value of nontimber forest products to Pendjari biosphere reserve dwellers in Benin - Vodouhê, F.G.; Coulibaly, O.; Greene, C.; Sinsin, B. (Springer, 2009)
This paper uses an indices method based on participant ranking of species to quantify use–values of Non-Timber Forest Products (NTFPs) and the socio-economic factors that influence these values for people living around the Pendjari Biosphere Reserve in Benin. There were 76 species identified that had a high index value to people. The 10 most valued species were Parkia biglobosa, Adansonia digitata, Vitellaria paradoxa, Tamarindus indica, Lannea microcarpa, Vitex doniana, Hibiscus asper, Melochia corchorifolia, Khaya senegalensis, and Diospyros mespiliformis. Species values were influenced by the vegetative form of the species as well as by the gender of a participant and his/her affiliation to the ethnic group. The study also illustrates that women had a preference for NTFP species with high commercial and nutritional values, while men preferred plants that provide construction material and medicine. Moreover, the ethnic group that historically had more contact and interaction with the vegetation valued NTFPs more than any other group. The difference in value attributed to species by people was also driven by the vertical transmission of ethnobotanical knowledge in the study area. For long-term biodiversity conservation, it will be useful to involve the needs of all of the local communities in the design of a management plan and focus attention on the most important species.